George Clark, The Criminal Laws of Texas. Comprising the Penal Code and Code of Criminal Procedure, as Published by Authority, with Annotations of All Decisions in Criminal Cases from Dallam to Eighth Court of Appeals Reports Inclusive, at 205-208, tit. 15, ch. 16, art. 610 (1881) - (:unkn) unknown (My University, 1881)
Any person who shall, within this State, fight a duel with deadly weapons, or send or accept a challenge to fight a duel with deadly weapons, either within the State or out of it, or who shall act as a second, or knowingly aid or assist in any manner those thus offending, shall be deemed guilty of a felony and upon conviction shall be punished by confinement in the penitentiary not less than two nor more than five years.
Keywords: DUELING